Romeo and Juliet before Shakespeare: four early stories of star-crossed love ; by Masuccio Salernitano, Luigi da Porto, Matteo Bandello, and Pierre Boaistuau - Prunster, Nicole (Renaissance and reformation texts in translation, 2000)
Mariotto and Ganozza / Masuccio Salernitano -- A tale about two noble lovers / Luigi da Porto -- The unfortunate death of two most wretched lovers / Matteo Bandello -- Of two lovers / Pierre Boaistuau